In vitro antifungal susceptibility of Candida spp. isolates from patients with chronic periodontitis and from control patients - Koga-Ito, Cristiane Yumi; Paiva Martins, Clélia Aparecida de; Loberto, Jussara Cia Sanches; Santos, Silvana Soléo Ferreira dos; Jorge, Antonio Olavo Cardoso [UNESP] (FapUNIFESP (SciELO), 2004)
Superinfection by Candida can be refractory to conventional periodontal treatments in specific situations, such as in immunocompromised patients. In these cases, the systemic therapy with antifungal drugs could be indicated. The aim of this study was to analyse antifungal susceptibility of Candida spp. strains isolated from chronic periodontitis patients and from control individuals. A total of 39 C. albicans isolates, 9 C. tropicalis, 2 C. glabrata and 5 Candida spp. from control individuals and 30 C. albicans, 3 C. tropicalis and 2 C. glabrata from periodontitis patients were tested. In the control group, 1 isolate of C. glabrata was resistant to ketoconazole and 1 Candida spp. was resistant to amphotericin B, ketoconazole and miconazole. Among the isolates of periodontitis group, 1 (3.33%) C. albicans isolate was resistant to flucytosine and ketoconazole. According to the obtained results, it could be concluded that fluconazole was the most effective drug against the several Candida species studied. There were not expressive differences in the susceptibility of isolates from periodontitis patients or from control individuals.
Keywords: antifungal agent; fluconazole; flucytosine; ketoconazole; miconazole; adult; Candida; case control study; drug effect; human; isolation and purification; microbiological examination; microbiology; middle aged; periodontitis; Adult; Antifungal Agents; Case-Control Studies; Fluconazole; Flucytosine; Humans; Ketoconazole; Miconazole; Microbial Sensitivity Tests; Middle Aged; Periodontitis